Cenepa: what the press wrote - Flores, Carlos E. (2017)
The Cenepa’s conflict between Peru and Ecuador (1995) was the last chapter of border disputes which finished with the signing of peace in 1998. Both countries defend its thesis and denied the another one. In this regard, it was discussed a question ¿what social or ideological representations were involved since the written press of both countries during the conflict? Based on the methodology of “ideological square” of Van Dijk was made an analysis of content to the information treatment of newspapers “El Comercio de Perú y Ecuador” to explain the perceptions or ideologies of each group which is done with respect to the another one from the written speech.